Prescribing pattern and drug utilization study in inpatients of department of Orthopaedics in a rural teaching hospital of Ujjain, Madhya Pradesh, India - Baghel, Ruchi; Adwal, Sandeep K.; Singh, Vivek; Chourishi, Ashutosh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug utilization study can increase our understanding of how drugs are being used. This study was done to evaluate the current drug prescribing trend in management of indoor patient of orthopaedic department and to comment on rationality of the prescribed medicines. Methods: This is a prospective observational study conducted for 12 months, in Chandrikaben Rashmikant Gardi Hospital, a 600 bedded tertiary care rural based, teaching hospital. Total 611 patients were included in this study. Results: Total 5416 drugs were prescribed in 611 prescriptions. Average number of drugs per prescription was 8.86. Average duration of prescription was 10.7 days. Percentage of drugs prescribed by generic name was 28.8%. Percentage of encounter with an Antibiotic prescribed was 60.23% i.e. out of 611 prescriptions antibiotics were prescribed in 368. Percentage of encounter with an Injection prescribed was 63% which means out of 611 prescriptions, injectables were prescribed in 385. Percentage of drugs prescribed from National Essential Medicine List was 52.63%. Percentage of drugs prescribed from WHO model List was 32.46%. Diclofenac (14.25%) was most commonly prescribed drug. Incidence of polypharmacy was quite high in context of Analgesics. Almost 40% of prescriptions had 2 drugs. Orally prescribed Analgesics were 62.6%, Injectables 34.38% and Topical 3.02%. Conclusions: This study reveals that the pattern of prescription in terms of rationality is poor. Special attention needs to be given to the irrational prescribing in terms of polypharmacy and long duration. Continuing medical education regarding appropriate use of drugs, knowledge of adverse effects and standard prescription guidelines will play pivotal role in rational prescription of drugs.